Institutional climate and evaluation of educational quality at Ie 7054 Villa María Del Triunfo. Lima. - Quiñones Huanca, Aydee (2024)
It is necessary to carry out research on the relationship between institutional climates and evaluation of educational quality in order to investigate whether there is a relationship between both variables in the educational environment. Primary students in Peru perform poorly on the ECE test. Especially Villa María del Triunfo IE 7054 in Lima. Teamwork is essential, as are intra and interpersonal relationships, dialogue, empathy and other variables. The study was conducted using quantitative methods, hypothesized deductive methods, sequential cross-sectional level, and descriptive correlational models. Two questionnaires were used containing 20 indicators validated by a panel of three expert judges and reliability measures using Cronbach's (alfa) coefficient. We have 80 teachers for the feasibility study. The data analysis used descriptive statistics and inferential statistics to test the hypothesis and found a significant statistical relationship between the two variables mentioned above because the level of quality of teacher training is insufficient, which is essential for a good institutional climate. The quality of the service provided. A correlation coefficient of R=.912 and a p value of 0.000 was obtained.